Ceria Nanoparticle Systems for Selective Scavenging of Mitochondrial, Intracellular, and Extracellular Reactive Oxygen Species in Parkinson's Disease. Issue 30 (22nd June 2018) - Kwon, Hyek Jin; Kim, Dokyoon; Seo, Kyungho; Kim, Young Geon; Han, Sang Ihn; Kang, Taegyu; Soh, Min; Hyeon, Taeghwan
Abstract: Oxidative stress induced by reactive oxygen species (ROS) is one of the critical factors that involves in the pathogenesis and progression of many diseases. However, lack of proper techniques to scavenge ROS depending on their cellular localization limits a thorough understanding of the pathological effects of ROS. Here, we demonstrate the selective scavenging of mitochondrial, intracellular, and extracellular ROS using three different types of ceria nanoparticles (NPs), and its application to treat Parkinson's disease (PD). Our data show that scavenging intracellular or mitochondrial ROS inhibits the microglial activation and lipid peroxidation, while protecting the tyrosine hydroxylase (TH) in the striata of PD model mice. These results indicate the essential roles of intracellular and mitochondrial ROS in the progression of PD. We anticipate that our ceria NP systems will serve as a useful tool for elucidating the functions of various ROS in diseases. Abstract : Oxidative stress : Mitochondrial, intracellular, and extracellular reactive oxygen species (ROS) have been selectively scavenged using three different types of ceria nanoparticles, and this technique has been applied to treat Parkinson's disease (PD). The data reveal the essential roles of intracellular and mitochondrial ROS on the progression of PD (TPP=triphenylphosphonium).